Vegetation in clear‐cuts depends on previous land use: a century‐old grassland legacy. Issue 22 (24th October 2014) - Jonason, Dennis; Ibbe, Mathias; Milberg, Per; Tunér, Albert; Westerberg, Lars; Bergman, Karl‐Olof
Abstract Plant species richness in central and northern European seminatural grasslands is often more closely linked to past than present habitat configuration, which is indicative of an extinction debt. In this study, we investigate whether signs of historical grassland management can be found in clear‐cuts after at least 80 years as coniferous production forest by comparing floras between clear‐cuts with a history as meadow and as forest in the 1870s in Sweden. Study sites were selected using old land‐use maps and data on present‐day clear‐cuts. Species traits reflecting high capacities for dispersal and persistence were used to explain any possible links between the plants and the historical land use. Clear‐cuts that were formerly meadow had, on average, 36% higher species richness and 35% higher richness of grassland indicator species, as well as a larger overall seed mass and lower anemochory, compared to clear‐cuts with history as forest. We suggest that the plants in former meadows never disappeared after afforestation but survived as remnant populations. Many contemporary forests in Sweden were managed as grasslands in the 1800s. As conservation of remaining grassland fragments will not be enough to reduce the existing extinction debts of the flora, these young forests offer opportunities for grassland restoration at large scales. Our study supports the concept of remnant populations and highlights the importance of considering historical land use for understanding the distribution of grassland plant species in fragmented landscapes, as well as for policy‐making and conservation.